Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Perilaku Siswa - Sari, Putri Maharani Anom; Mugiyono, Mugiyono (Juwara: Jurnal Wawasan dan Aksara, 2024)
This study aims to explore the significant impact of Islamic education learning on student behavior. The methodology employed in this study is a quantitative approach through sample selection. Sample selection among students was conducted using purposive sampling methods. The findings of this study indicate that there is a moderate impact of Islamic education learning on student behavior, with an analyzed influence level of 0.593 or 59.34%. In conducting the analysis, the product moment correlation technique was applied. From the Product Moment "r" Value Table, it was revealed that with a df of 31, the Product Moment "r" values obtained at a significance level of 5% are 0.355 and at 1% are 0.456. Comparing the "ro" value achieved by the researcher, which is 0.593, with the "rt" values, each being 0.355 and 0.456, it is evident that "ro" exceeds "rt" at both the 5% and 1% significance levels. Consequently, the Null Hypothesis is rejected and the Alternative Hypothesis is accepted. This indicates a significant impact of the Islamic Education Learning on Student Behavior at SDN Cipinang 03 Pagi Jakarta.